HxMoO3−y nanobelts: an excellent alternative to carbon electrodes for high performance mesoscopic perovskite solar cells. Issue 4 (4th January 2019) - Zhang, Hua; Wang, Huan; Yang, Yinglong; Hu, Chen; Bai, Yang; Zhang, Teng; Chen, Wei; Yang, Shihe
Abstract : The H x MoO3− y nanobelts as electrode has been firstly demonstrated with efficiency up to 14.5% in mesoscopic perovskite solar cells. This work thus opens up a new direction for developing electrode materials for more efficient mesoscopic perovskite solar cells. Abstract : Carbon-based hole-conductor-free perovskite solar cells (C-PSCs) are considered as a promising photovoltaic technology toward commercialization, owing to their low cost and superior stability. However, efforts to further improve their efficiency have been hampered by the hole-extraction barrier at the Schottky contact between carbon and the perovskite. A conventional approach to resolve this issue is incorporating a hole-transport material (HTM) into the mesoscopic skeleton or chemical modification of the carbon electrode. Here, we show an innovative strategy that uses solution-processed hydrogen molybdenum bronze (H x MoO3− y ) nanobelts, an n-type HTM with high work function and electrical conductivity, as the sole electrode material to enhance the hole-extraction process and realize efficient PSCs for the first time. The mesoscopic cell configuration of FTO/c-TiO2 /m-TiO2 /m-Al2 O3 /H x MoO3− y with perovskite infiltration delivered a champion power conversion efficiency (PCE) of 14.5%, which compares favorably with 13.3% of typical high temperature C-PSCs. This increase in cell efficiency stems primarily from the enhancement in open circuit voltage and short circuit current, which is due to the H x MoO3− y electrode with more favorable energy alignment and higher hole-extraction ability than the carbon electrode. These results show the potential of H x MoO3− y nanobelts as an efficient electrode for realizing high-performance mesoscopic PSCs.